Which national park attributes attract international tourists? A Sri Lankan case study. Issue 7 (November 2022) - Suresh, Kanesh; Wilson, Clevo; Quayle, Annette; Khanal, Uttam; Managi, Shunsuke
This study assesses how and in what circumstances tourists' perceived value of nature-based tourism (NBT) attributes differ among various types of national parks. A novel discrete choice experiment is used employing data collected from 343 international tourists in four national parks in Sri Lanka. We find that the improvements in frequency of large species' encounters, habitat quality and proximity to encountered wildlife produce greater utility. A surprising finding is that tourists are shown to prefer to spend only a limited amount of time at national parks. They also tend to choose less-visited parks that have large mammals for which they would be willing to pay more compared to those national parks that are more frequently visited. Our article contributes to the empirical evidence that time is a key factor that determines the tourism destination choice and less-visited parks offer considerable potential for future growth of tourism.